Effects of erosive challenge on the morphology and surface properties of luting cements - Brenna Louise Cavalcanti GONDIM; Isabella Cavalcante MEDEIROS; Bruna Palmeira COSTA; Hugo Lemes CARLO; Rogério Lacerda dos SANTOS; Fabíola Galbiatti de CARVALHO
Abstract Introduction Few studies investigated the surface properties of luting cements after erosive challenge. Objective To evaluate the surface roughness (Ra), Vickers hardness (VHN) and morphology of 4 luting cements after erosive challenge. Material and method Twenty specimens of each cement were prepared (4×2mm) and divided into experimental (erosive challenge) and control (artificial saliva) groups (n=10): Rely X U200 (U200); Rely X ARC (ARC); Ketac Cem Easy Mix (Ketac) and Zinc phosphate (ZnP). The erosive challenge was performed by four daily erosive cycles (90s) in a cola drink and 2 h in artificial saliva over 7 days. Ra and VHN readings were performed before and after erosion. The percentage of hardness loss (%VHN) was obtained after erosion. The surface morphology was analyzed by scanning electron microscopy (SEM). ANOVA, Tukey and Student-T tests were used (α=0.05). Result After erosion, all luting cements had increase in Ra values and U200 and ZnP groups had the highest %VHN. After saliva immersion, only U200 and ZnP groups had significant increases in Ra values and there were no significant differences among the groups in %VHN. SEM analysis showed that Ketac and ZnP groups had rough and porous surfaces, and U200 group had higher resin matrix degradation than ARC group. Conclusion Erosive challenge with a cola drink affected the surface properties of all luting cements.